Pemberdayaan Masyarakat Penerima PKH untuk Mengendalikan Perilaku Konsumtif dan Pinjaman Online di Nagari Kumango - Arief Irvan; Shinta Oktavia; Darmansyah Darmansyah; Silvana Nurdiani; Alfi Syukri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted in Nagari Kumango, Sungai Tarab District, Tanah Datar Regency, focusing on empowering beneficiaries of the Program Keluarga Harapan (PKH) through a socio-cultural approach. The program was motivated by the low level of public understanding regarding the purpose of social assistance, the increasing trend of digital-driven consumptive behavior, and the high vulnerability to online loans and online gambling. The objective of this program was to enhance community awareness and capacity in managing social assistance wisely while strengthening socio-economic resilience. The methods applied included socialization, participatory education, group discussions, and mentoring based on local Minangkabau cultural values. The results indicate an improvement in community understanding in distinguishing between needs and wants, better household financial management, and increased awareness of digital consumption risks. The socio-cultural approach proved effective in strengthening community solidarity and participation. Therefore, integrating local cultural values is a crucial strategy in achieving sustainable community empowerment in the digital era.